2012
DOI: 10.1111/j.1748-1716.2012.02417.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between shear rate and flow‐mediated dilation is altered by acute exercise

Abstract: The weak relationship in FMD and SR after exercise suggests that these data should not be normalized following aerobic exercise. Thus, endothelial function was attenuated after a continuous 30-min aerobic exercise session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…Indeed, such factors have been shown to mediate postexercise FMD responses in various patient populations. 38,[40][41][42] Repetitive increases in flow during habitual exercise training have been shown to improve FMD, which is indicative of enhanced NO-mediated EF. 24,43,44 There is a plethora of research demonstrating that aerobic training enhances EF in overweight and obese adults, 45,46 but few studies have investigated the specific effects of resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such factors have been shown to mediate postexercise FMD responses in various patient populations. 38,[40][41][42] Repetitive increases in flow during habitual exercise training have been shown to improve FMD, which is indicative of enhanced NO-mediated EF. 24,43,44 There is a plethora of research demonstrating that aerobic training enhances EF in overweight and obese adults, 45,46 but few studies have investigated the specific effects of resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the direction of the FMD change is not consistent between studies, as previous investigations have demonstrated increases (Harris et al 2008;Harvey et al 2005;Tinken et al 2010;Tyldum et al 2009), decreases (Harris et al 2008;Llewellyn et al 2012;McGowan et al 2006;Rognmo et al 2008;Silvestro et al 2002), and no change Harvey et al 2005;Rognmo et al 2008;Silvestro et al 2002) in FMD following an exercise bout. However, the evidence from the 2 within-subject studies suggest exercise duration and intensity may not influence the magnitude of the post-exercise responses, as similar changes in endothelialdependent function were observed within a given sample following different exercise bouts.…”
Section: The Role Of Different Exercise Boutsmentioning
confidence: 55%
“…Investigations of the acute endothelial responses to a single bout of exercise have employed a variety of exercise interventions including endurance exercise Harris et al 2008;Harvey et al 2005;Jones et al 2010;Llewellyn et al 2012;Tyldum et al 2009), interval exercise (Tyldum et al 2009), sub-maximal and maximal exercise (Silvestro et al 2002), isometric handgrip exercise (McGowan et al 2006;Tinken et al 2010), and resistance exercise (Phillips et al 2011). Of these investigations, only 2 have compared the effect of different exercise bouts by employing within-subject study designs (Harris et al 2008;Tyldum et al 2009).…”
Section: The Role Of Different Exercise Boutsmentioning
confidence: 99%
See 2 more Smart Citations